2017
DOI: 10.1186/s13756-017-0265-1
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and genotypic characteristics of ESBL and AmpC producing organisms associated with bacteraemia in Ho Chi Minh City, Vietnam

Abstract: BackgroundBroad-spectrum antimicrobials are commonly used as empirical therapy for infections of presumed bacterial origin. Increasing resistance to these antimicrobial agents has prompted the need for alternative therapies and more effective surveillance. Better surveillance leads to more informed and improved delivery of therapeutic interventions, potentially leading to better treatment outcomes.MethodsWe screened 1017 Gram negative bacteria (excluding Pseudomonas spp. and Acinetobacter spp.) isolated betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 23 publications
3
14
0
1
Order By: Relevance
“…Thus, a low prevalence (9.4%) of AmpC β-lactamase producers was registered by this study. These findings corroborate well with other studies that reported relatively low prevalence (0.5%-30%) of coproduction of ESBLs and AmpCs [29][30][31][32] E. coli (81.2%) isolates were more predominant than K. pneumoniae (18.8%) among the archived samples. This is in agreement with other studies that attempted to establish the prevalence of ESBLs producing Enterobacteriaceae in Uganda [9,10,25,27].…”
Section: Discussionsupporting
confidence: 92%
“…Thus, a low prevalence (9.4%) of AmpC β-lactamase producers was registered by this study. These findings corroborate well with other studies that reported relatively low prevalence (0.5%-30%) of coproduction of ESBLs and AmpCs [29][30][31][32] E. coli (81.2%) isolates were more predominant than K. pneumoniae (18.8%) among the archived samples. This is in agreement with other studies that attempted to establish the prevalence of ESBLs producing Enterobacteriaceae in Uganda [9,10,25,27].…”
Section: Discussionsupporting
confidence: 92%
“…Nevertheless, this lack of growth is useful in clinical practice because it signifies that these microorganisms are, in principle, not relevant for the diagnosis. E. cloacae and K. aerogenes were resistant to FOX and susceptible to both FEP and IMP, in line with previous studies (32,(42)(43)(44)(45). Some isolates grown on the medium exhibited susceptibility to FOX and IMP with variable resistance to FEP, a similar phenotype to that of microorganisms with ESBL resistance, which may also have been present.…”
Section: Retrospective Studysupporting
confidence: 87%
“…Our findings identified cytotoxic activity among over 50% of A. veronii group and A. hydrophila isolates as well as 30% of MDR isolates, thus posing a potential health risk. With hypervirulent strains of A. hydrophila jeopardizing aquaculture (72) and ESBL-producing strains associating with bacteremia (73,74), it is critical that we continue to assess antibiotic resistance with pathogenic phenotypes to elaborate on the potential health risk. Previously, our group and others have identified a correlation with Aeromonas strains encoding serine protease and aerolysin genes with cytotoxic phenotypes (21,75) and disease (11,76).…”
Section: Discussionmentioning
confidence: 99%